Micropolar Nanofluid Flow in a Vertical Porous Channel: Entropy Generation Analysis - Ontela, Surender; Tlau, Lalrinpuia (Journal of Applied Nonlinear Dynamics, 2026)
The present analysis consists of a mixed convection micropolar nanofluid flow in a porous medium-filled upright channel. The mathematical equations governing the flow consists of second order differential equations for the velocity, micropolarity and temperature. These equations have been solved utilizing the Homotopy Analysis Method (HAM). The series solution expression is thus obtained for the velocity, temperature and micro-rotation profiles. The value of the entropy generation and the irreversibility ratio are determined. The effect of specific flow parameters on the generation of entropy and irreversibility are displayed graphically and deliberated fervently.